To the issue of classification of contracts into consensual and real contracts - Вавженчук, Сергій Ярославович (Problems of legality, 2020)
In the article on the basis of analysis of current and former Ukrainian legislation and doctrinal sources are considered some issues of classification of civil law contracts into consensual and real contracts. Approach to divide contracts into two aforementioned groups originates in Roman law; however, its sufficient theoretical model is produced only in XIX century. In Soviet period this method to classify contracts was sharply criticized. Current Civil code of Ukraine uses both types (models): consensual and real contracts. Contract is to be treated as consensual unless the opposite is prescribed in civil legislation. In order to conclude real contract, in addition to sufficient agreement, transfer of property or execution of other action is needed. Such transfer of property or other action are not considered as a part of fulfillment of contractual obligation; they take place at the stage of contract formation and are prerequisite for the very existence of real contract. Based on these considerations, direct application of norm regulating contractual transfer of ownership to conclusion of real contract is complicated and cannot be conducted without certain adjustments. Another issue related to the formation of real contract is transfer of non-documentary securities and non-cash money. These civil law objects following a common approach are not regarded as things (res). Therefore, transfer of non-documentary securities and non-cash money in a procedure of formation of real contract cannot be qualified as transfer of property in its traditional meaning.